As percepções de professoras e professores que ensinam Matemática sobre o processo de ensino e de aprendizagem de estudantes com Deficiência Intelectual - Barbosa, Débora Resende Pereira (2022)
This qualitative research is inserted in the field of Mathematics Education, more specifically in the area of pedagogical practices and teacher training from the perspective of Inclusive Education. Our objectives are: 1) to know the training trajectory of teachers who teach Mathematics from an inclusive perspective and 2) to analyze the teaching practices of teachers who teach Mathematics when working with students with Intellectual Disabilities. We sought to answer the research question: what perceptions do female and male mathematics teachers have about the process of teaching and learning mathematics with students with Intellectual Disabilities? To achieve the objectives and answer the research question, a course entitled "Virtual Conversation Circle: Mathematics and Intellectual Disability - sharing experiences" was developed with three teachers and a mathematics teacher from southern Minas Gerais who worked or worked with students with intellectual disabilities from an inclusive perspective. The course had as methodology the focus group perspective (WELLER, 2006) with a duration of thirty hours, distributed in four synchronous meetings developed in Google Meet and three asynchronous ones using the “Campus Virtual” of a Public Federal University. The instruments used for data constitution were screen and voice recorders, logbook and reflective records. As theoretical support, we relied on Vigotski's (2000, 2003, 2007) knowledge of teachers and teaching and learning from a cultural historical perspective, which served as subsidies for the analysis. We chose to use narrative analysis based on Bertaux (2010) and Bolívar, Domingo and Fernandez (2001). The study allowed us to observe the various strategies used by teachers who teach mathematics for school inclusion and meaningful learning of mathematical concepts. Our study pointed out that the use of manipulative materials such as golden material, popsicle sticks, games, and the use of ICTs, when available, can be important tools for teaching and learning mathematics for students with Intellectual Disabilities.